Internet services as a support to library services - Vrana, Radovan (Array, 2013)
The internet plays an important role in creation and functioning of selected library services. Web 2.0 and social software enriched online communication between librarians and library users on the internet and introduced new library services supported by the social software. Users are given an opportunity to use library through participatory, user-driven services. Internet services also helped libraries to present their existing services and to develop new services on the internet by use of Web 2.0 tools. Here are presented selected well known internet services that can be used as a support and or an extension of the existing library services and be of help in creation of new library services. The purpose is to familiarize students with the role of the internet in transformation of libraries under the influence of the internet and participatory paradigm of use of library services in the digital world.